KOMPETENSI MAHASISWA (STUDI MAHASISWA PADA UNIVERSITAS KRISTEN KRIDA WACANA) - Evans Garey; Selly Selly (MANASA, 2012)
Now a days employer tends to look for employee who has competence not only in  academic area but also in soft skills area. Krida Wacana Christian University (UKRIDA) has been developing soft skills program since 2009. UKRIDA has done lots of activities regards to self development. The approach which is used for developing students competence in UKRIDA is The Base Competence. This research tried to measure students competence. Acknowledging students competence can be a foundation to the students competencies development. This research is using quantitative method. There are 399 students who participate in this research. All participants are first year under graduate students. This research use Making The March questionnaire with 63 item. From the four competencies in base competencies: mobilizing innovation and change, and managing people and task considered o be average to high. UKRIDA first year students competencies is a reflection of academic and social background. The Bases of Competence give a framework for developing students soft skills. Students can prepare them selves early for a career development in order to be ready for work place challenges and a better future.